2018
DOI: 10.1002/nbm.3956
|View full text |Cite
|
Sign up to set email alerts
|

Rheological determinants for simultaneous staging of hepatic fibrosis and inflammation in patients with chronic liver disease

Abstract: The purpose of this study is to investigate the use of fundamental rheological parameters as quantified by MR elastography (MRE) to measure liver fibrosis and inflammation simultaneously in humans. MRE was performed on 45 patients at 3 T using a vibration frequency of 56 Hz. Fibrosis and inflammation scores were obtained from liver biopsies. Biomechanical properties were quantified in terms of complex shear modulus G as well as shear wave phase velocity c and shear wave attenuation α. A rheological fractional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…Although the range of frequencies investigated here is small (0.5-2Hz), the models presented in this study are applicable for other frequencies as well. The fractional order is related to the frequency response, and the value identified in this study ( = 0.2 ) is in good agreement with literature findings (Liu and Bilston 2000;Jordan et al 2011;Sinkus et al 2018;Asbach et al 2008). Thus, by choosing the nonlinear parameters presented in Fig.…”
Section: Study Limitationssupporting
confidence: 91%
See 2 more Smart Citations
“…Although the range of frequencies investigated here is small (0.5-2Hz), the models presented in this study are applicable for other frequencies as well. The fractional order is related to the frequency response, and the value identified in this study ( = 0.2 ) is in good agreement with literature findings (Liu and Bilston 2000;Jordan et al 2011;Sinkus et al 2018;Asbach et al 2008). Thus, by choosing the nonlinear parameters presented in Fig.…”
Section: Study Limitationssupporting
confidence: 91%
“…For diagnosis purposes, elastography is a technique that depends on the underlying tissue properties in order to assess the presence of disease (Fovargue et al 2018). In vivo magnetic resonance elastography (MRE) has shown that the existence of liver inflammation and fibrosis gives higher stiffness measurements (Huwart et al 2006;Sinkus et al 2018). However, coexisting diseases (Mueller et al 2010) and the bias introduced by large deformations on elastography measurements (Capilnasiu et al 2019) can further complicate the diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings support earlier work that on a physical level it untangles the effects of inflammation and fibrosis. Indeed, by modifying the rheological model used to derive biomechanical properties from the raw data, Sinkus et al in that article showed how fibrosis and inflammation act on specific and different components of the model . The current article's confirmation of these effects is a promising development, as the noninvasive estimation of inflammatory activity takes a further step towards clinical application.…”
mentioning
confidence: 75%
“…That seems often to be the case for elastography data. 20,21 Publications report observed values for the compliance of both models also follows a Mittag-Leffler function. That means that the creep time-and frequency-spectral functions of the two models will also be similar.…”
Section: Time-and Frequency-spectral Functionsmentioning
confidence: 99%